일차성 식도운동장애에서 신경성 산화질소-합성효소 유전자 다형성에 대한 연구 - 이태희; Tae Hee Lee; 이준성; Joon Seong Lee; 김연수; Yun Soo Kim; 이종은; Jong Eun Lee; 조은영; Eun Young Cho; 정인섭; In Seop Jung; et al. (Journal of neurogastroenterology and motility, 2008)
목적: 일차성 식도운동장애는 내인성 억제신경의 기능의 문제와 연관이 있다고 보고되고 있다. 억제신경에 가장 중요한 신경전달물질은 산화질소(Nitric oxide, NO)로 NO 합성효소(NO synthase)에 의해 합성된다. 본 연구의 목적은 nNOS 유전자 다형성과 일차성 식도운동장애의 연관성을 규명하고자 하였다. 대상 및 방법: 전체 168명(남자 76명, 여자 92명; 중앙 연령 49세) 중 36명의 위식도역류질환 환자를 포함한 일차성 식도운동장애 환자군 129명(식도이완불능증 25명, 미만성식도경련 6명, 호두까기 식도 37명, 비특이적 식도운동장애 17명, 고압성하부식도조임근 3명, 저압성하부식도조임근 5명)과 건강한 39명의 대조군을 대상으로 하였다. 본 연구에서 유전자 다형성을 보였던 세 nNOS 유전자 SNP (rs374147, rs2682826, rs3782218)를 이용하여 위식도역류질환을 포함한 일차성 식도운동장애군과 대조군 사이에 차이가 있는지 비교하였다. 결과: nNOS의 유전자 다형성(rs374147, rs2682826, rs3782218)은 위식도역류질환을 포함한 일차성 식도운동장애군과 대조군 간에 유전자형, 대립유전자 빈도 분포 및 일배체형 분석에서 유의한 차이는 없었다. 결론: nNOS 유전자 다형성은 일차성 식도운동장애의 병태생리에 영향을 미치지 않는 것으로 보인다. Background/Aims: Primary esophageal motility disorders (PEMDs) are caused by different degrees of inhibitory dysfunction. Nitric oxide (NO) is a major inhibitory neurotransmitter. Some studies have shown that NO production is regulated by NO synthase (NOS) polymorphism. The aim of this study was to assess whether neuronal NOS (nNOS) gene polymorphism is associated with a susceptibility of primary esophageal motility disorders. Methods: Total 168 persons (76 men and 92 women; median age 49 years) were enrolled in the study. The subjects were divided into two groups: PEMD group and control group. PEMD group was composed of 25 achalasia, 6 diffuse esophageal spasm, 37 nutcracker esophagus, 3 hypertonic lower esophageal sphincter (LES), 5 hypotonic LES, 17 nonspecific esophageal motility disorder and 36 gastroesophageal reflux disease. The comparisons of genotype and allele frequencies of NOS gene single nucleotide polymorphisms (rs374147, rs2682826, and rs3782218) were made between PEMD and control group. Results: There were no significant differences in the allele frequencies and genotype among the groups. Haplotypic analysis showed no significant differences among the groups. Conclusions: Our results suggest that functional polymorphisms of neuronal NOS (nNOS) gene are not involved in the pathophysiology of primary esophageal motility disorders. (Kor J Neurogastroenterol Motil 2008;14:108-114)